"Mushroom" Autologous Partial Ossicular Replacement Prosthesis: Long-term Results. Issue 1 (January 2021) - Malhotra, Manu; Priya, Madhu; Bhardwaj, Abhishek; Tyagi, Amit Kumar; Kumar, Amit; Varshney, Saurabh; Malhotra, Rashmi
Abstract : Objective: Evaluate a new autologous mushroom-shaped cortical bone partial ossicular replacement prosthesis (MPORP) for cost-effective and sustainable hearing results. Study Design: Prospective study. Setting: Tertiary care center. Patients: Forty-two patients suffering from chronic otitis media with intact superstructure of the stapes and partially or completely eroded incus. Interventions: Group-1 (n = 24) underwent only tympanoplasty with MPORP; group-2 (n = 18) underwent intact canal wall mastoidectomy (ICW) with MPORP. Main Outcome Measures: Hearing results were evaluated using a four frequency average (measured at 0.5, 1, 2, 3 kHz) pure tone air conduction (PTA), air-bone gap (ABG), and word recognition scores (WRS) after 3, 6, and 12 months and compared with preoperative results. Results: Overall, successful rehabilitation of ABG to 20 dB or less was achieved in 92% of patients. Mean postoperative ABG was 15.35 ± 4.18 dB showing mean improvement of 23.89 ± 5.95 dB. In group-1, mean postoperative ABG was 18.47 ± 3.65 dB, showing an improvement of 25.92 ± 5.3 dB. In group-2, mean postoperative ABG was 18.47 ± 3.65 dB showing an improvement of 20.14 ± 4.96 dB. Hearing improvement in all the cases together and both the groups checked separately was statistically significant (paired t test, p  < 0.001). Group 1 had, on average, 5 dB better hearing than group 2 (unpaired t test, p  > 0.05). Conclusion: The MPORP is obtainable from the local site, easily constructed, bio-compatible, cost-effective, less bulky, adequately rigid for sound transmission, magnetic resonance imaging (MRI) compatible, and provides sustainable hearing gain because it has better chances of integration with the head of stapes. Abstract : Supplemental Digital Content is available in the text